128 Road traffic deaths among 29 high-income countries, 2015 and 2019. (20th November 2022) - Yellman, Merissa A; Lee, Robin; Sauber-Schatz, Erin K
Abstract : Background: Road traffic deaths (RTDs) are a leading cause of death throughout the world. Methods: To gauge progress in reducing RTDs, we used data from the International Road Traffic and Accident Database to calculate population-based death rates (per 100, 000 population), distance-based death rates (per billion vehicle kilometers traveled), and vehicle-based death rates (per 10, 000 registered vehicles), as well as average rates and average percent changes from 2015 to 2019 for 29 high-income countries with populations >1, 000, 000 residents and for which data were available. Results: In 2019, the U.S. had the highest population-based RTD rate (11.1) compared with 28 other high-income countries; the U.S. rate was 2.3 times higher than the average rate (4.8). The U.S. also had a higher distance-based death rate (6.9) than the average rate for 20 other high-income countries (5.7) and a higher vehicle-based death rate (1.21) than the average rate for 27 other high-income countries (0.78). From 2015 to 2019, Switzerland had the largest percent decrease (-28.7%) in population-based RTD rates, whereas Denmark had the largest percent increase (9.0%). The U.S. remained relatively stable with a 0.1% percent increase. Conclusion: Many high-income countries with low RTD rates and large reductions have implemented effective strategies (e.g., lower blood alcohol concentration limits and speed reduction strategies). Emphasizing a Safe System approach—which accounts for human error and helps protect all road users—and implementing proven strategies can help reduce RTDs in the U.S. and other countries. Learning Outcomes: Learn about road safety progress in 29 high-income countries.